Government Strategy & Policies for the United Arab Emirates for Energy Transition & Net Zero Targets - Murtada Ahmed (Communications of International Proceedings, 2022)
This article looks at the trend of the new direction and emerging challenges to adhere to the UN Sustainability Development Goals (SDGs) in the energy sector.  Also, it considers how it is planned for incorporating the energy transition in their future visions and country plans of the hydrocarbon net exporting countries. Mainly it will be focusing on an example from the east hemisphere countries in the middle east that are classified as net hydrocarbon exporters, namely the United Arab Emirates. It will try to clarify the approach taken by UAE in facing the challenges related to the Energy Transition and net zero targets, how it evolved overtime and what will be the future direction for the implementation and what are the vehicles to achieve this.
Keywords: Strategy; Energy Transition; Net Zero; Climate Change; Policy; Sustainability; Decarbonizing.